Determinants of Millennial Generation Entrepreneurial Interest in an Islamic Economic Perspective - Mutia Alif Cahyani; Indra, Indra (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to spread the impact of Islamic spirituality in entrepreneurship, personal motivation, social environment, as well as education and learning on interest in entrepreneurship in active and productive age groups. The data analysis method used is SmartPLS (Partial Least Squares Structural Equation Modeling). Primary data was collected through an online questionnaire distributed to all respondents in the Jabodetabek area (Jakarta, bogor, depok, tangerang, bekasi).